An improved authentication scheme for H.264/SVC and its performance evaluation over non-stationary wireless mobile networks - ZHAO, Yifan (Institutional Knowledge at Singapore Management University, 2012)
In this paper, a bit stream-based authentication scheme for H.264/Scalable Video Coding (SVC) is proposed. The proposed scheme seamlessly integrates cryptographic algorithms and erasure correction codes (ECCs) to SVC video streams such that the authenticated streams are format compliant with the SVC specifications and preserve the three dimensional scalability (i. e., spatial, quality and temporal) of the original streams. We implement our scheme on a smart phone and study its performance over a realistic bursty packet-lossy wireless mobile network. Our analysis and experimental results show that the scheme achieves very high verification rates with lower communication overhead and much smaller decoding delay compared with the existing solutions.